Cryogenic strength improvement by utilizing room-temperature deformation twinning in a partially recrystallized VCrMnFeCoNi high-entropy alloy - Y. H. Jo (Nature Portfolio, 2017)
CrMnFeCoNi high entropy alloys have high fracture toughness at cryogenic temperatures due to deformation twinning but twinning is not active in this alloy at room temperature. Here authors optimize composition and thermomechanical treatments to introduce non-recrystallized grains, producing high yield strength while maintaining good ductility.